The Predictive Value of Integrated Pulmonary Index after Off-Pump Coronary Artery Bypass Grafting: A Prospective Observational Study - Fot, Evgenia V.; Izotova, Natalia N.; Yudina, Anjelika S.; Smetkin, Aleksei A.; Kuzkov, Vsevolod V.; Kirov, Mikhail Y. (Frontiers in Medicine, 2017)
Background The early warning scores may increase the safety of perioperative period. The objective of this study was to assess the diagnostic and predictive role of Integrated Pulmonary Index (IPI) after off-pump coronary artery bypass grafting (OPCAB). Materials and Methods Forty adult patients undergoing elective OPCAB were enrolled into a single-center prospective observational study. We assessed respiratory function using IPI that includes oxygen saturation, end-tidal CO2, respiratory rate, and pulse rate. In addition, we evaluated blood gas analyses and hemodynamics, including ECG, invasive arterial pressure, and cardiac index. The measurements were performed after transfer to the intensive care unit, after spontaneous breathing trial and at 2, 6, 12, and 18 h after extubation. Results and Discussion The value of IPI registered during respiratory support correlated weakly with cardiac index (rho = 0.4; p = 0.04) and ScvO2 (rho = 0.4, p = 0.02). After extubation, IPI values decreased significantly, achieving a minimum by 18 h. The IPI value ≤9 at 6 h after extubation was a predictor of complicated early postoperative period (AUC = 0.71; p = 0.04) observed in 13 patients. Conclusion In off-pump coronary surgery, the IPI decreases significantly after tracheal extubation and may predict postoperative complications.